Functional traits of cryptogams in Mediterranean ecosystems are driven by water, light and substrate interactions - Giordani, Paolo; Incerti, Guido; Rizzi, Guido; Rellini, Ivano; Nimis, Pier Luigi; Modenesi, Paolo (JOURNAL OF VEGETATION SCIENCE, 2014)
Question Poikilohydric organisms can survive desiccation without damage and recover soon after re-wetting. In this work we explore the realized niches of epilithic, poikilohydric organisms, i.e. lichenized and lichenicolous fungi and bryophytes, grouped into 15 functional guilds based on growth form, reproductive strategy and photosynthetic traits. We hypothesize that in Mediterranean ecosystems, the distribution of these guilds is controlled by water availability and solar radiation, together with characteristics of the substrate. Location Western Sardinia (Italy). The area hosts Mediterranean Quercus ilex forests on basaltic substrata within an agroforestry landscape. Methods The presence or absence of species from each guild was recorded in 1025 small quadrats (10x10cm). Four environmental variables were measured: solar radiation, microtopography (potential water run-off), substrate roughness and number of cracks. The occurrence of each guild was related to environmental variables using non-parametric multiplicative regression, and ecological niches of the guilds were derived from those models. Results The occurrence of all functional guilds varied significantly according to the selected environmental variables. In most cases, solar radiation was the most important variable; TI was included first in the model of two sorediate guilds, whereas four sexually reproducing functional guilds had surface relief as first variable. The growth forms were separated along a gradient of increasing solar radiation, whereas water run-off and surface roughness mainly discriminated reproductive strategies and photobionts. Vegetatively reproducing guilds with other photobionts than Euphyta-like pigments were confined to the border of the ecological space, defined by gradients of environmental factors, which was largely occupied by more competitive, sexually reproducing organisms. Conclusions Functional traits of epilithic poikilohydric organisms were associated with ecological adaptations to the stressful environment of Mediterranean outcrops. We showed that their response in terms of probability of occurrence is coherent with quantitative gradients of solar radiation and water availability at the micro-scale.
Keywords: bryophytes; functional traits; lichens; Photosynthetic strategy; Reproductive strategy

Litter quality assessed by solid state 13C NMR spectroscopy predicts decay rate better than C/N and Lignin/N ratios - Bonanomi, Giuliano; Incerti, Guido; Giannino, Francesco; Mingo, Antonio; Lanzotti, Virginia; Mazzoleni, Stefano (Soil Biology and Biochemistry, 2013)
Predictions of litter decomposition rates are critical for modelling biogeochemical cycling in terrestrial ecosystems and forecasting organic carbon and nutrient stock balances. Litter quality, besides climatic conditions, is recognized as a main factor affecting decay rates and it has been traditionally assessed by the C/N and lignin/N ratios of undecomposed materials. Here, solid state 13 C NMR spectroscopy and proximate chemical analysis have been used to characterize litter organic C in a litterbag experiment with 64 different litter types decomposing under controlled conditions of temperature and water content. A statistical comparative analysis provided evidence that C/N and lignin/N ratios, showing different trends of correlation with decay rates at different decomposition stages, can be used to describe the quality of undecomposed litter, but are unable to predict mass loss of already decomposed materials. A principal component regression (PCR) model based on 13 C NMR spectra, ﬁtted and cross-validated by using either two randomly selected sets of litter types, showed highly ﬁtting predictions of observed decay rates throughout the decomposition process. The simple ratio 70e75/52e57 corresponding to Oalkyl C of carbohydrates and methoxyl C of lignin, respectively, showed the highest correlation with decay rate among different tested parameters. These ﬁndings enhance our understanding of litter quality, and improve our ability to predict decomposition dynamics. The 13 C NMR-based 70e75/52e57 ratio is proposed as an alternative to C/N and lignin/N ratios for application in experimental and modelling work
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: C stocks; C-cycle; decomposition; litter quality; litterbag; Principal component regression; Proximate cellulose and lignin

Litter decomposition in Mediterranean ecosystems: Modelling the controlling role of climatic conditions and litter quality - Incerti, Guido; Bonanomi, Giuliano; Giannino, Francesco; Rutigliano, Flora Angela; Piermatteo, Daniela; Castaldi, Simona; De Marco, Anna; Fierro, Angelo; Fioretto, Antonietta; Maggi, Oriana; Papa, Stefania; Persiani, Anna Maria; et al. (Applied Soil Ecology, 2011)
A new process-based model of litter decomposition, characterized by detailed climatic data input and simple litter quality parameters, is proposed. Compared to existing litter carbon models, speciﬁc implementations for temperature and moisture limiting effects have been adopted. The model is capable to represent decomposition processes in Mediterranean ecosystems, with summer drought slowing down, even at optimal temperatures, the litter decay rates of sclerophyll plants whose leaf masses are rich in structural compounds and low in N content. The model was calibrated by a best ﬁtting procedure of two different datasets. First, unpublished results of litterbag experiments on leaf litter of 9 Mediterranean species, decomposing under controlled and not limiting temperature and water conditions, have been used to estimate the decay rate dependency from litter quality that was deﬁned by only three initial C pools (labile, stable and recalcitrant compounds) instead of traditional N-based indices. Second, a set of published data from three medium-term ﬁeld experiments on a single species, Phillyrea angustifolia, decomposing under different climatic conditions, have been used to estimate the limiting effects of temperature and moisture. The model was then validated against published data on seven other species and showed a correct reproduction ofthemajor patterns of littermass loss during decomposition processes of other seven different Mediterranean species. The model simulations, satisfactory for different litter types under a wide range of climatic conditions, suggest that factors which were not taken into account, such as initial litter N contents, microclimatic variations related to stand structure, soil chemistry and texture, and microbial communities, are not very signiﬁcant for assessing decomposition dynamics in Mediterranean ecosystems. The minimal requirements of input data, the simple structure, and the easiness of parameterisation make our model, among the many other available litter carbon models, an attractive alternative for different research purposes, at least for Mediterranean ecosystems.
Keywords: C model; C/N ratio; Initial C pools; process-based model; Semi-arid ecosystems; System dynamics